High-strength rough-surface winding core pipe and processing technology thereof
By adopting high-strength core rolling tubes of modified glass fiber and composite carbon fiber, the problem of brittle cracking in conventional core rolling tubes during transportation is solved, and higher mechanical strength and wear resistance are achieved, ensuring product quality and winding quality .
Patent Information
- Application Number
- CN202411568017.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The core tubes of conventional thermosetting materials are prone to brittle due to weight concentration during transportation, which affects product quality, and poor winding quality will affect the winding quality of subsequent multi-layer products.
Using a high-strength core rolling tube composed of polyvinyl alcohol, epoxy resin, modified glass fiber and composite carbon fiber, a cross-linking network is formed by combining dopamine-modified glass fiber and polyhexahydrotriazine-hydroxyferric oxide composite carbon fiber. Structure to improve the mechanical strength and wear resistance of the core tube.
It significantly improves the strength and wear resistance of the core tube, reduces the risk of brittle cracking, ensures the stability and quality of the product during transportation, and improves the winding quality.
Smart Images

Figure BDA0005119749240000091 
Figure BDA0005119749240000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of core-rolled tubes, and in particular to a high-strength core-rolled tube with a rough surface and a processing technology thereof. Background Art
[0002] The core tube is a tool used for winding products such as film and copper foil. By placing the core tube in the winding equipment, the material to be wound on the surface of the core tube first. When the equipment is started, the material can be wound on the core tube.
[0003] Conventional roll cores are made of thermosetting materials and are processed by extrusion molding. The surfaces of some roll cores also need to be polished to remove burrs and other impurities on the surface of the roll cores, thereby improving the quality of product winding. When winding, the operator manually pre-rolls the film or copper foil product on the roll core until the roll core can drive the product to be wound. With the development of the logistics and transportation industry, the demand for the transportation of rolled products is also increasing. In order to prevent the rolled products from directly contacting the vehicle or the ground during transportation, some support frames are usually set at both ends of the length direction of the roll core to keep the products on the roll core separated from the ground.
[0004] However, conventional heat-fixed materials have poor strength and rigidity, especially for longer core tubes. During storage and transportation, the support frames at both ends will cause the product to be off the ground. At this time, the weight of the product is all on the core tube. Some products are heavy, so during transportation, the core tube is prone to cracking, affecting product quality. At the same time, for some film products, during the rolling process, if the first layer of the base product has poor winding quality, it will affect the winding quality of subsequent multi-layer products. Summary of the invention
[0005] In order to improve the strength of a rolled core tube, the present application provides a high-strength rolled core tube with a rough surface and a processing technology thereof.
[0006] The present application provides a high-strength rough-surface rolled core tube and its processing technology using the following technical solutions: In the first aspect, the present application provides a high-strength rough-surface rolled core tube, which adopts the following technical solution: A high-strength rough-surface rolled core tube comprises the following components in parts by weight: 200-240 parts of polyvinyl alcohol, 80-100 parts of epoxy resin, 30-36 parts of glass fiber composite material, 42-50 parts of epoxy soybean oil composite, 8-10 parts of dispersant, 6-8 parts of toughening agent; The glass fiber composite material comprises modified glass fiber and composite carbon fiber.
[0007] By adopting the above technical scheme, a glass fiber composite material prepared by modified glass fiber and composite carbon fiber is added to the system, which can improve the overall strength of the core tube. The modified glass fiber is an inorganic metal material with excellent performance and good mechanical strength. The composite carbon fiber also has good mechanical strength. After the two are combined, they can synergistically improve the overall strength and mechanical properties of the core tube system. At the same time, the composite carbon fiber can improve the lack of wear resistance of the glass fiber, thereby improving the performance of the two. At the same time, the glass fiber composite material can further connect the various components of the core tube to make the system connection tighter, thereby improving the strength of the core tube.
[0008] Preferably, the modified glass fiber is prepared by the following method: Dopamine is added to Tris buffer to obtain a dopamine dispersion, glass fibers are added to the dopamine dispersion, stirred for reaction, and then the glass fibers are filtered, washed, and dried to obtain modified glass fibers.
[0009] By adopting the above technical scheme, dopamine has the adhesion property of mussels and can generate polydopamine in a weak alkaline environment. After the glass fiber is modified by dopamine, dopamine is attached to the surface of the glass fiber, which can improve the compatibility of the glass fiber. At the same time, the interaction of the modified glass fiber in the system is significantly improved, so that the bonding effect of the system is enhanced. The modified glass fiber can adhere to epoxy resin on the surface, thereby improving the surface roughness of the glass fiber, thereby improving the overall stability and mechanical properties of the system.
[0010] Preferably, the dopamine concentration in the dopamine dispersion is 0.9-1.1 mg / ml.
[0011] By adopting the above technical solution, preferably the concentration of dopamine is within the above range, which can further enhance the modification effect of dopamine on the surface of the glass fiber.
[0012] Preferably, the composite carbon fiber comprises carbon fiber, polyhexahydrotriazine and iron oxyhydroxide.
[0013] By adopting the above technical solution, after the carbon fiber is modified by polyhexahydrotriazine and hydroxy iron oxide, the strong covalent skeleton of hexahydrotriazine possessed by the carbon fiber has better stability, thereby greatly improving the performance of the carbon fiber. After hydroxy iron oxide grows on the surface of the carbon fiber, the combination of the three further improves the comprehensive performance of the carbon fiber.
[0014] Preferably, the composite carbon fiber is prepared by the following method: The ferric chloride is dissolved in water, and ammonium fluoride is added while stirring to obtain a composite solution, and the carbon fiber is added to the composite solution. After the reaction, the carbon fiber is washed and dried to obtain hydroxy iron oxide-carbon fiber; 1,3-bis(4'-aminophenoxy)benzene, 4-aminoindole, N-methylpyrrolidone, polytetrafluoroethylene wax and formaldehyde are mixed and ultrasonically dispersed to obtain a polyhexahydrotriazine-polytetrafluoroethylene wax mixed solution, and the hydroxy iron hydroxide-carbon fiber is added to the polyhexahydrotriazine-polytetrafluoroethylene wax mixed solution, and pre-cured to obtain a composite carbon fiber.
[0015] By adopting the above technical scheme, oxyhydroxide iron is grown on the surface of carbon fiber by a hydrothermal method, and polyhexahydrotriazine is wrapped on the surface of carbon fiber to which oxyhydroxide iron is attached, so that a large number of nano-granular protrusions appear on the surface of the system, thereby further improving the mechanical properties and wear resistance of the system; indole straight chains are introduced to construct dynamic crosslinks with metal cations, thereby further improving the strength of the carbon fiber, thereby improving the overall stability of the system.
[0016] Preferably, the mass ratio of ferric chloride to ammonium fluoride in the composite solution is (7.2-7.4):1.
[0017] By adopting the above technical solution, the mass ratio between ferric chloride and ammonium fluoride in the composite solution is preferably within the above range, thereby further improving the overall stability of the prepared carbon fiber.
[0018] Preferably, the polyhexahydrotriazine-polytetrafluoroethylene wax loading on the surface of the ferric hydroxide-carbon fiber is 147-153 mg / cm 2 .
[0019] By adopting the above technical solution, preferably the loading amount of the polyhexahydrotriazine-polytetrafluoroethylene wax is within the above range, the stability of the prepared composite carbon fiber can be further improved.
[0020] Preferably, the epoxy soybean oil complex is prepared in the following manner: 2,6-di(2-furanylmethylene)-1-cyclohexanone is mixed with tetrahydrofuran, sodium cyclopentadienyl is added, and the mixture is dissolved in water after stirring. After standing, the oil phase is removed for extraction, and then dilute hydrochloric acid is added until no precipitation is generated. After standing, the supernatant is removed, and the modified cross-linking agent is obtained by suction filtration, washing, and drying; the modified cross-linking agent is mixed with anhydrous ethanol, sodium ethoxide is added, and the mixture is reacted by magnetic stirring, and the mixture is washed after suction filtration and dried to obtain a sodium carboxylate composite cross-linking agent; the epoxy soybean oil, the sodium carboxylate composite cross-linking agent, and zinc acetylacetonate are mixed, and the mixture is stirred evenly, and the reaction is stirred to obtain the epoxy soybean oil complex.
[0021] By adopting the above technical scheme, polyvinyl chloride contains a lot of chlorine atoms, and the interaction between molecular chains is strong, so it has some defects. The bio-based plasticizer epoxy soybean oil rich in epoxy groups is used as a co-cross-linking component, and cyclopentadienyl sodium is introduced at the same time. β-hydroxy ester bonds are generated through epoxy-carboxylic acid esterification reaction. Part of the carboxyl groups can undergo esterification reaction with the epoxy groups of the epoxy soybean oil, and the other part of the carboxyl groups react with the active chlorine on the polyvinyl chloride, so that the polyvinyl chloride and the epoxy soybean oil are cross-linked together to form a cross-linked network structure, which further enhances the overall stability of the system, and the mechanical properties are further improved.
[0022] Preferably, the sodium carboxylate composite cross-linking agent is 2.8-3% of the mass of the epoxidized soybean oil.
[0023] By adopting the above technical solution, preferably the mass of the sodium carboxylate composite cross-linking agent is within the above range, which can further improve the comprehensive performance of the prepared epoxidized soybean oil composite.
[0024] In a second aspect, the present application provides a processing technology for a high-strength rough-surface rolled core tube, which adopts the following technical solution: A processing technology for a high-strength rough-surface rolled core tube comprises the following steps: Polyvinyl alcohol, epoxy resin, glass fiber composite material, epoxy soybean oil composite, dispersant and toughening agent are mixed and added into a twin-screw extruder for melt blending and granulation. The product is extruded into a mold, impurities on the surface of the core tube are removed, and a high-strength core tube is obtained after cutting.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Adding glass fiber composite components and epoxy soybean oil composites to the system can further improve the comprehensive performance of polyvinyl chloride. The glass fiber composite material includes modified glass fiber and composite carbon fiber. The modified glass fiber is an inorganic metal material with excellent performance and good mechanical strength. The composite carbon fiber also has good mechanical strength. After the two are combined, they can synergistically improve the overall mechanical strength and wear resistance of the winding core tube system, and enable the various components in the winding core tube to be further connected, thereby improving the stability of the system and further improving the strength of the winding core tube; 2. After the surface of the glass fiber is modified by dopamine, the overall compatibility of the glass fiber is improved, thereby improving the bonding strength of the system. The carbon fiber is treated with polyhexahydrotriazine and ferric hydroxide to obtain a composite carbon fiber with good mechanical strength and wear resistance. After the modified glass fiber is combined with the composite carbon fiber, the overall strength of the system is further improved; 3. Epoxidized soybean oil, a bio-based plasticizer rich in epoxy groups, is used as a co-cross-linking component, and cyclopentadienyl sodium is introduced at the same time. β-hydroxy ester bonds are generated through epoxy-carboxylic acid esterification reaction. Some carboxyl groups can undergo esterification reaction with the epoxy groups of the epoxy soybean oil, and the other part of the carboxyl groups reacts with the active chlorine on the polyvinyl chloride, thereby cross-linking the polyvinyl chloride and the epoxy soybean oil to form a cross-linked network structure, further improving the overall stability of the system. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments: Raw material description: All raw materials in the examples can be obtained commercially; among them, the toughening agent is chlorinated polyethylene, and the dispersant is BYK-W940.
[0027] Example 1 Preparation of modified glass fiber: The glass fiber was treated in a muffle furnace at 500°C for 1 hour to remove impurities on the surface of the glass fiber. Dopamine was added to Tris buffer to obtain a dopamine dispersion with a dopamine concentration of 0.9 g / mL. The glass fiber was added to the dopamine dispersion and stirred at 300 r / min for 24 hours. The glass fiber was then filtered and washed with deionized water and dried in an oven at 95°C for 3 hours to obtain modified glass fiber.
[0028] Preparation of composite carbon fiber: 43.9 g of ferric chloride was dissolved in 300 g of deionized water, and the mixture was stirred at a speed of 200 r / min for 30 min. 6.1 g of ammonium fluoride was added while stirring and the mixture was stirred for 3 h to obtain a composite solution. 60 g of carbon fiber was added to the composite solution so that the carbon fiber was completely immersed in the composite solution. The mixture was reacted at 100 ° C for 16 h, and then cooled to 25 ° C. After washing with deionized water, the mixture was dried at 60 ° C for 8 h to obtain iron oxyhydroxide-carbon fiber. 16 g of 1,3-bis(4'-aminophenoxy)benzene (CAS No.: 2479-46-1) and 0.2 g of 4-aminoindole (CAS No.: 5192-23-4), 320 g of N-methylpyrrolidone (CAS No.: 872-50-4), 4 g of polytetrafluoroethylene wax (CAS No.: 9002-84-0) and 6 g of formaldehyde were mixed and ultrasonically dispersed for 10 min to obtain a polyhexahydrotriazine-polytetrafluoroethylene wax mixture. Hydroxy iron hydroxide-carbon fiber was added to the polyhexahydrotriazine-polytetrafluoroethylene wax mixture, and then pre-cured in an oven at 100 ° C for 3 min. The pre-curing was repeated until the surface loading of polyhexahydrotriazine-polytetrafluoroethylene wax was 147 mg / cm 2 , and obtain composite carbon fiber.
[0029] Preparation of epoxidized soybean oil complex: 0.46 g of 2,6-di(2-furylmethylene)-1-cyclohexanone (CAS No.: 893-00-5) was mixed with 50 g of tetrahydrofuran (CAS No.: 109-99-9), and 4.54 g of cyclopentadienyl sodium (CAS No.: cyclopentadienyl sodium) was added under nitrogen atmosphere, and the mixture was stirred and poured into a plastic bucket filled with dry ice. After the dry ice evaporated, the product was dissolved in deionized water, and after standing, the oil phase was removed and extracted, and then 10% dilute hydrochloric acid was added until no precipitation was produced. After standing, the supernatant was removed, and the mixture was filtered and washed with deionized water, and then in The modified cross-linking agent was dried at 50°C; the modified cross-linking agent was mixed with anhydrous ethanol, 80g of sodium ethoxide was added, the mixture was reacted by magnetic stirring, then filtered, washed with deionized water and dried at 60°C to obtain a sodium carboxylate composite cross-linking agent; 50g of epoxy soybean oil (CAS No.: 8013-07-8), 1.4g of the sodium carboxylate composite cross-linking agent and zinc acetylacetonate (CAS No.: 14024-63-6) were mixed and stirred evenly, nitrogen was then introduced, the temperature was raised to 140°C, and the mixture was stirred in an oil bath, and the reaction was performed for 4h to obtain an epoxy soybean oil complex.
[0030] Preparation of high-strength rolled core tube: 200 g of polyvinyl alcohol, 80 g of epoxy resin, 30 g of glass fiber composite material, 42 g of epoxy soybean oil complex, 8 g of dispersant and 6 g of toughening agent were mixed, and added into a twin-screw extruder for melt blending and granulation. The temperature of the extruder barrel was set to 200°C, the head temperature was set to 200°C, the die temperature was set to 190°C, and the rotation speed was set to 40 r / min. The product was extruded into a mold, impurities on the surface of the core tube were removed, and a high-strength core tube was obtained after cutting.
[0031] Example 2 Preparation of modified glass fiber: The glass fiber was treated in a muffle furnace at 500°C for 1 hour to remove impurities on the surface of the glass fiber. Dopamine was added to Tris buffer to obtain a dopamine dispersion with a dopamine concentration of 1.1 g / mL. The glass fiber was added to the dopamine dispersion and stirred at 300 r / min for 24 hours. The glass fiber was then filtered and washed with deionized water and dried in an oven at 95°C for 3 hours to obtain modified glass fiber.
[0032] Preparation of composite carbon fiber: 44.05 g of ferric chloride was dissolved in 300 g of deionized water, and the mixture was stirred at a speed of 200 r / min for 30 min. 5.95 g of ammonium fluoride was added while stirring for 3 h to obtain a composite solution. 60 g of carbon fiber was added to the composite solution so that the carbon fiber was completely immersed in the composite solution. The mixture was reacted at 100 ° C for 16 h, and then cooled to 25 ° C. After washing with deionized water, the mixture was dried at 60 ° C for 8 h to obtain oxyhydroxide iron-carbon fiber. 16 g of 1 ,3-bis(4'-aminophenoxy)benzene, 0.2 g of 4-aminoindole, 320 g of N-methylpyrrolidone, 4 g of polytetrafluoroethylene wax and 6 g of formaldehyde were mixed and ultrasonically dispersed for 10 min to obtain a polyhexahydrotriazine-polytetrafluoroethylene wax mixture. Hydroxy iron hydroxide-carbon fiber was added to the polyhexahydrotriazine-polytetrafluoroethylene wax mixture, and then pre-cured in an oven at 100 ° C for 3 min. The pre-curing was repeated until the surface polyhexahydrotriazine-polytetrafluoroethylene wax loading was 153 mg / cm 2 , and obtain composite carbon fiber.
[0033] Preparation of epoxidized soybean oil complex: 0.46 g of 2,6-di(2-furanylmethylene)-1-cyclohexanone was mixed with 50 g of tetrahydrofuran, and 4.54 g of cyclopentadienyl sodium was added under nitrogen atmosphere. After stirring, the mixture was poured into a plastic bucket filled with dry ice. After the dry ice evaporated, the product was dissolved in deionized water. After standing, the oil phase was removed and extracted. Then, 10% dilute hydrochloric acid was added until no precipitation was produced. After standing, the supernatant was removed, filtered, washed with deionized water, and then heated at 50 °C. The modified cross-linking agent was dried under an environment to obtain a modified cross-linking agent; the modified cross-linking agent was mixed with anhydrous ethanol, 80 g of sodium ethoxide was added, magnetic stirring was used for reaction, and then suction was filtered, the mixture was washed with deionized water, and then dried at 60°C to obtain a sodium carboxylate composite cross-linking agent; 50 g of epoxy soybean oil, 1.6 g of the sodium carboxylate composite cross-linking agent and zinc acetylacetonate were mixed and stirred evenly, nitrogen was then introduced, the temperature was raised to 140°C, and stirring was carried out under oil bath conditions, and the epoxy soybean oil complex was obtained after reacting for 4 hours.
[0034] Preparation of high-strength rolled core tube: 240 g of polyvinyl alcohol, 100 g of epoxy resin, 36 g of glass fiber composite material, 50 g of epoxy soybean oil compound, 10 g of dispersant and 8 g of toughening agent were mixed, and added into a twin-screw extruder for melt blending and granulation. The temperature of the extruder barrel was set to 200°C, the head temperature was set to 200°C, the die temperature was set to 190°C, and the rotation speed was set to 40 r / min. The product was extruded into a mold, impurities on the surface of the core tube were removed, and a high-strength core tube was obtained after cutting.
[0035] Example 3 Preparation of modified glass fiber: The glass fiber was treated in a muffle furnace at 500°C for 1 hour to remove impurities on the surface of the glass fiber. Dopamine was added to Tris buffer to obtain a dopamine dispersion with a dopamine concentration of 1 g / mL. The glass fiber was added to the dopamine dispersion and stirred at 300 r / min for 24 hours. The glass fiber was then filtered and washed with deionized water and dried in an oven at 95°C for 3 hours to obtain modified glass fiber.
[0036] Preparation of composite carbon fiber: 43.98 g of ferric chloride was dissolved in 300 g of deionized water, and the mixture was stirred at a speed of 200 r / min for 30 min. 6.02 g of ammonium fluoride was added while stirring for 3 h to obtain a composite solution. 60 g of carbon fiber was added to the composite solution so that the carbon fiber was completely immersed in the composite solution. The mixture was reacted at 100 ° C for 16 h, and then cooled to 25 ° C. After washing with deionized water, the mixture was dried at 60 ° C for 8 h to obtain oxyhydroxide iron-carbon fiber. 16 g of 1 ,3-bis(4'-aminophenoxy)benzene, 0.2 g of 4-aminoindole, 320 g of N-methylpyrrolidone, 4 g of polytetrafluoroethylene wax and 6 g of formaldehyde were mixed and ultrasonically dispersed for 10 min to obtain a polyhexahydrotriazine-polytetrafluoroethylene wax mixture. Hydroxy iron hydroxide-carbon fiber was added to the polyhexahydrotriazine-polytetrafluoroethylene wax mixture, and then pre-cured in an oven at 100 ° C for 3 min. The pre-curing was repeated until the surface loading of polyhexahydrotriazine-polytetrafluoroethylene wax was 150 mg / cm 2 , and obtain composite carbon fiber.
[0037] Preparation of epoxidized soybean oil complex: 0.46 g of 2,6-di(2-furanylmethylene)-1-cyclohexanone was mixed with 50 g of tetrahydrofuran, and 4.54 g of cyclopentadienyl sodium was added under nitrogen atmosphere. After stirring, the mixture was poured into a plastic bucket filled with dry ice. After the dry ice evaporated, the product was dissolved in deionized water. After standing, the oil phase was removed and extracted. Then, 10% dilute hydrochloric acid was added until no precipitation was produced. After standing, the supernatant was removed, filtered, washed with deionized water, and then heated at 50 °C. The modified cross-linking agent was dried under an environment to obtain a modified cross-linking agent; the modified cross-linking agent was mixed with anhydrous ethanol, 80 g of sodium ethoxide was added, magnetic stirring was used for reaction, and then suction was filtered, and the mixture was washed with deionized water and dried at 60° C. to obtain a sodium carboxylate composite cross-linking agent; 50 g of epoxy soybean oil, 1.5 g of the sodium carboxylate composite cross-linking agent and zinc acetylacetonate were mixed and stirred evenly, and then nitrogen was introduced, the temperature was raised to 140° C., and stirring was carried out under oil bath conditions. After reacting for 4 hours, an epoxy soybean oil complex was obtained.
[0038] Preparation of high-strength rolled core tube: 220g of polyvinyl alcohol, 90g of epoxy resin, 33g of glass fiber composite material, 46g of epoxy soybean oil complex, 9g of dispersant and 7g of toughening agent were mixed, and added into a twin-screw extruder for melt blending and granulation. The temperature of the extruder barrel was set to 200°C, the head temperature was set to 200°C, the die temperature was set to 190°C, and the rotation speed was set to 40r / min. The product was extruded into a mold, impurities on the surface of the core tube were removed, and a high-strength core tube was obtained after cutting.
[0039] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing the modified glass fiber, the dopamine concentration of the dopamine dispersion is 0.5 mg / mL.
[0040] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing the modified glass fiber, the dopamine concentration of the dopamine dispersion is 1.6 mg / mL.
[0041] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing iron oxyhydroxide-carbon fiber, the amount of ferric chloride used is 43.59 g and the amount of ammonium fluoride used is 6.41 g.
[0042] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that when preparing iron oxyhydroxide-carbon fiber, the amount of ferric chloride used is 44.32 g, and the amount of ammonium fluoride used is 5.68 g.
[0043] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that the loading amount of polyhexahydrotriazine-polytetrafluoroethylene wax on the surface of the composite carbon fiber is 135 mg / cm 2 .
[0044] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that the loading amount of polyhexahydrotriazine-polytetrafluoroethylene wax on the surface of the composite carbon fiber is 165 mg / cm 2 .
[0045] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the glass fiber composite, the mass of the modified glass fiber is 20 g, and the mass of the composite carbon fiber is 20 g.
[0046] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the glass fiber composite, the mass of the modified glass fiber is 10 g, and the mass of the composite carbon fiber is 30 g.
[0047] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that when preparing the epoxy soybean oil composite, 2 g of the sodium carboxylate composite cross-linking agent is used.
[0048] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that when preparing the epoxy soybean oil composite, 4g of sodium carboxylate composite crosslinking agent is used. Embodiment 14 Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that dopamine is not used to modify the glass fiber in Example 14.
[0049] Embodiment 15 Example 15 is based on Example 3. The difference between Example 15 and Example 3 is that in Example 15, when preparing composite carbon fibers, the composite carbon fibers are replaced with iron oxyhydroxide-carbon fibers.
[0050] Example 16 Example 16 is based on Example 3. The difference between Example 16 and Example 3 is that in Example 16, when preparing composite carbon fibers, ordinary carbon fibers are directly treated with a mixed liquid of polyhexahydrotriazine-polytetrafluoroethylene wax to obtain composite carbon fibers.
[0051] Comparative Example 1 Comparative Example 1 is based on Example 3. When preparing the glass fiber composite in Comparative Example 1, the composite carbon fiber is replaced with ordinary carbon fiber.
[0052] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the glass fiber composite is replaced with an equal amount of modified glass fiber.
[0053] Comparative Example 3 Comparative Example 3 is based on Example 3, and in Comparative Example 3, the modified glass fiber is replaced by an equal amount of composite carbon fiber.
[0054] Comparative Example 4 Comparative Example 4 is based on Example 3, and in Comparative Example 4, the epoxidized soybean oil complex is replaced with ordinary epoxidized soybean oil.
[0055] Performance testing The following performance tests were performed on the samples of Examples 1-16 and Comparative Examples 1-4: (1) Bending strength test Taking GB / T 9341-2008 as the testing standard, the bending properties of the samples were tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0056] (2) Impact resistance test Based on GB / T 1043.1-2008 as the testing standard, the impact strength performance test was carried out on the samples. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0057] (3) Wear resistance test According to GB / T3960-2016 as the testing standard, the wear resistance of the samples was tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0058] Table 1 Performance test results of samples of Examples 1-16 and Comparative Examples 1-4 Combined with Table 1, it can be seen that the bending strength of Examples 1-3 is 110Mpa or above, indicating that the core tube prepared in this application has good bending strength performance, and the impact resistance of Examples 1-3 is 52KJ / m 2 And above, it shows that the core tube prepared in the present application has good impact resistance, so the core tube prepared in the present application has good strength; the mass wear of Examples 1-3 is 39 mg or less, which shows that the core tube prepared in the present application has good wear resistance.
[0059] The concentrations of the dopamine dispersions in Examples 4 and 5 are not within the range defined in the present application. When the concentration of dopamine is too low, too little dopamine is coated on the surface of the glass fiber, and the bonding strength of the system is difficult to further increase. When the concentration of dopamine is too high, the excessively thick dopamine will fall off from the surface of the glass fiber, thereby weakening the interaction between the glass fiber and the system. Therefore, the performance of Examples 4 and 5 is reduced.
[0060] The mass ratios of ferric chloride to ammonium fluoride in Examples 6 and 7 are not within the range defined in the present application. When the content of ferric chloride is too much or too little, it will affect the stability of the ferric hydroxide oxide attached to the surface of the carbon fiber, and affect the subsequent adhesion of the polyhexahydrotriazine-polytetrafluoroethylene wax. Therefore, the performance of Examples 6 and 7 are both reduced.
[0061] The loading amounts of polyhexahydrotriazine-polytetrafluoroethylene wax on the surface of the composite carbon fiber in Examples 8 and 9 are not within the range defined in the present application. When the loading amount of polyhexahydrotriazine-polytetrafluoroethylene wax is too much, the carbon fiber will be too thick, thereby causing entanglement of the system chain segments and affecting the stability of the system. When the loading amount of polyhexahydrotriazine-polytetrafluoroethylene wax is too little, it is difficult to form a stable cross-linked structure between the carbon fiber, hexahydrotriazine-polytetrafluoroethylene wax and ferric hydroxide, which will also affect the stability of the system. Therefore, the performance of Examples 8 and 9 are both reduced.
[0062] The mass ratios of the modified glass fiber and the composite carbon fiber in Examples 10 and 11 are adjusted. When the amount of the modified glass fiber is too much or too little, the bonding properties of the prepared glass fiber composite will be affected, thereby affecting the overall stability of the system.
[0063] The usage amounts of sodium carboxylate composite crosslinking agent in Examples 12 and 13 are not within the scope defined in the present application. When the content of sodium carboxylate composite crosslinking agent is too little and the degree of crosslinking is too small, it is difficult to further improve the performance of the system. When the content of sodium carboxylate composite crosslinking agent is too large, the crosslinking agent is difficult to completely disperse and the stability of the system is reduced. Therefore, the performances of Examples 12 and 13 are both reduced.
[0064] In Example 14, the glass fiber is not modified, and the compatibility of the unmodified glass fiber in the system is difficult to further improve, so the binding performance is reduced, and thus the performance of Example 14 is reduced.
[0065] In Example 15, only oxyhydroxide iron-carbon fiber and modified glass fiber were used for compounding, and in Example 16, ordinary carbon fiber and polyhexahydrotriazine-polytetrafluoroethylene wax mixed liquid were directly treated. Both of them are difficult to form a stable three-dimensional network structure, and the strength improvement performance of carbon fiber is reduced. Therefore, the performance of Example 15 and Example 16 are both reduced.
[0066] In Comparative Example 1, only ordinary carbon fiber and modified glass fiber are combined, and the strength of the carbon fiber that has not been partially composited decreases, and the wear resistance is difficult to be further improved, so the performance of Comparative Example 1 decreases.
[0067] No composite carbon fiber was added in Comparative Example 2, and no modified glass fiber was added in Comparative Example 3. It is difficult to synergistically improve the overall strength of the system by using only a single fiber, so the performance of Comparative Examples 2 and 3 are both reduced.
[0068] In Comparative Example 4, the epoxy soybean oil complex was replaced with ordinary epoxy soybean oil, but it was difficult to further improve the strength of the entire system, so the performance of Comparative Example 4 was reduced.
[0069] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A high-strength rough-surface rolled core tube, characterized in that: The composition comprises the following components in parts by weight: 200-240 parts of polyvinyl alcohol, 80-100 parts of epoxy resin, 30-36 parts of glass fiber composite material, 42-50 parts of epoxy soybean oil composite, 8-10 parts of dispersant, 6-8 parts of toughening agent; The glass fiber composite material comprises modified glass fiber and composite carbon fiber.
2. The high-strength rough-surface rolled core tube according to claim 1, characterized in that: The modified glass fiber is prepared by the following method: Dopamine is added to Tris buffer to obtain a dopamine dispersion, glass fibers are added to the dopamine dispersion, stirred for reaction, and then the glass fibers are filtered, washed, and dried to obtain modified glass fibers.
3. The high-strength rough-surface rolled core tube according to claim 2, characterized in that: The dopamine concentration in the dopamine dispersion is 0.9-1.1 mg / mL.
4. The high-strength rough-surface rolled core tube according to claim 1, characterized in that: The composite carbon fiber comprises carbon fiber, polyhexahydrotriazine and iron oxyhydroxide.
5. The high-strength rough-surface rolled core tube according to claim 4, characterized in that: The composite carbon fiber is prepared by the following method: The ferric chloride is dissolved in water, and ammonium fluoride is added while stirring to obtain a composite solution, and the carbon fiber is added to the composite solution. After the reaction, the carbon fiber is washed and dried to obtain hydroxy iron oxide-carbon fiber; 1,3-bis(4'-aminophenoxy)benzene, 4-aminoindole, N-methylpyrrolidone, polytetrafluoroethylene wax and formaldehyde are mixed and ultrasonically dispersed to obtain a polyhexahydrotriazine-polytetrafluoroethylene wax mixed solution, and the hydroxy iron hydroxide-carbon fiber is added to the polyhexahydrotriazine-polytetrafluoroethylene wax mixed solution, and solidified to obtain a composite carbon fiber.
6. The high-strength rough-surface rolled core tube according to claim 5, characterized in that: The mass ratio of ferric chloride to ammonium fluoride in the composite solution is (7.2-7.4):
1.
7. The high-strength rough-surface rolled core tube according to claim 5, characterized in that: The polyhexahydrotriazine-polytetrafluoroethylene wax loading amount on the surface of the hydroxyferric hydroxide-carbon fiber is 147-153 mg / cm 2 .
8. The high-strength rough-surface rolled core tube according to claim 1, characterized in that: The epoxidized soybean oil composite is prepared in the following manner: Mix 2,6-di(2-furanylmethylene)-1-cyclohexanone and tetrahydrofuran, add cyclopentadienyl sodium, stir and dissolve in water, stand and remove the oil phase for extraction, then add dilute hydrochloric acid until no precipitation is generated, stand and remove the supernatant, filter, wash and dry to obtain a modified cross-linking agent; The modified crosslinking agent is mixed with anhydrous ethanol, sodium ethoxide is added, magnetic stirring is performed for reaction, the mixture is filtered, washed, and dried to obtain a sodium carboxylate composite crosslinking agent; epoxy soybean oil, the sodium carboxylate composite crosslinking agent and zinc acetylacetonate are mixed, stirred evenly, and reacted by stirring to obtain an epoxy soybean oil complex.
9. The high-strength rough-surface rolled core tube according to claim 1, characterized in that: The sodium carboxylate composite cross-linking agent accounts for 2.8-3% of the mass of the epoxidized soybean oil.
10. A processing technology for the high-strength rough-surface rolled core tube according to claim 1, characterized in that: The steps include: Polyvinyl alcohol, epoxy resin, glass fiber composite material, epoxy soybean oil composite, dispersant and toughening agent are mixed and added into a twin-screw extruder for melt blending and granulation. The product is extruded into a mold, impurities on the surface of the core tube are removed, and a high-strength core tube is obtained after cutting.